{The clandestine uterus: Or how the uterus escapes detection prior to puberty} - Michala, L.; Aslam, N.; Conway, G.S.; Creighton, S.M. (BJOG: An International Journal of Obstetrics and Gynaecology, 2010)
Uterine agenesis is one of the differential diagnoses in adolescent girls with delayed menstruation. It may also be suspected earlier in childhood during investigations for other genitourinary conditions. However, accurate confirmation that the uterus is absent can be extremely difficult before puberty because of its small size. We describe ten girls referred to a specialist centre with a presumed diagnosis of an absent uterus which was later found to be incorrect. We conclude that imaging should be undertaken by clinicians with experience in management of this age group and in some girls it may be necessary to delay final diagnosis until after puberty. © 2009 RCOG BJOG An International Journal of Obstetrics and Gynaecology.
Keywords: Amenorrhoea; Puberty; Uterus